A study on factors that influence customers intention to purchase hybrid cars in Malaysia / Maswadi Aziz and Mohd Nazrin Nawi - Aziz, Maswadi; Nawi, Mohd Nazrin (Faculty of Business and Management, 2014)
The purpose of this study was to determine the significance factors that influence customers intention to purchase hybrid cars in Malaysia. The variables consists cost, environmental concern and brand are stated as independent variables for this study. The respondents were 100 employers and workers around Kelana Jaya and Putrajaya. The finding showed that cost, environmental concern and brand have influence on customers intention to purchase hybrid cars in Malaysia. All variables show positive relationship towards the customers intention to purchase hybrid cars.This study refers to primary data and also secondary data for supporting the sampling technique. Meanwhile, the researcher use questionnaire as the method to collect all the data from sample respondents in accomplishing the research objectives. While the data for this study was analyzed using multiple statistical procedures: mean point value, standard deviation, and correlation analysis. The result of the study presented in this research agrees that cost, environmental concern and brand influenced customers intention to purchase hybrid cars. This study can be seen as a foreword to a more detailed study to be carrying by future research on factors that influence customers intention to purchase hybrid cars in Malaysia.